(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The primary treatment of non-mutant, unresectable advanced non-small cell lung cancer(NSCLC) is mainly based on dual Platinum-based chemotherapy, adding immune checkpoint inhibitor to chemotherapy resulting in a higher response rate and survival compared with chemotherapy alone. Objectives: Evaluation of efficacy and safety of chemotherapy in combination with Pembrolizumab regimen in patients with stage IV NSCLC without diver mutations. Study subjects: All patients with stage IV NSCLC treated with Pembrolizumab at the Oncology Department of Thong Nhat Hospital from 1/2019 met the selection criteria. Methods: Retrospective descriptive case series in 1/2019 and cut-off data on 1/6/2023. Results: we enrolled 33 patients treated with chemotherapy combination pembrolizumab regimen. In this study, the response rate was 45.5%, the complete response was 8%; median time to treatment failure (TTF) 9 months; median overall survival 21 months; one case of grade 3 interstitial pneumonia, two cases of hepatitis, one case of diabetes, anemia and thrombocytopenia well controlled. Conclusion: Treatment of stage IV NSCLC with chemotherapy combination Pembrolizumab regimen is effective and safe.